2014
DOI: 10.1371/journal.pone.0116465
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Faecalibacterium prausnitzii from Calves and Piglets

Abstract: The goal of our study was to isolate and characterize Faecalibacterium prausnitzii from fecal samples of healthy calves and piglets, in order to develop a novel probiotic for livestock animals. We identified 203 isolates of Faecalibacterium sp., which were clustered in 40 genetically distinct groups. One representative isolate from each cluster was selected for further characterization. The concentrations of the short chain fatty acids (SCFA) acetate, butyrate, propionate and isobutyrate in the culture media w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 41 publications
4
47
0
1
Order By: Relevance
“…Similarly, members of the Faecalibacterium decreased in abundance as the availability of their preferred substrates changed. Faecalibacterium can metabolize acetate to produce butyrate (44), the major VFA involved in stimulating the growth and differentiation of colonocytes (45). Acetate availability in the calf GIT is mainly driven by carbohydrate fermentation by bacteria such as Blautia and Bacteroides.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, members of the Faecalibacterium decreased in abundance as the availability of their preferred substrates changed. Faecalibacterium can metabolize acetate to produce butyrate (44), the major VFA involved in stimulating the growth and differentiation of colonocytes (45). Acetate availability in the calf GIT is mainly driven by carbohydrate fermentation by bacteria such as Blautia and Bacteroides.…”
Section: Discussionmentioning
confidence: 99%
“…The optimal pH for F. prausnitzii growth ranges between 5.7 and 6.7 (Lopez-Siles et al, 2012;Foditsch et al, 2014), the range of pH found in the colon. Although there are differences in tolerance between strains in the pH range of 5-5.7 (Lopez-Siles et al, 2012), no growth was observed at pH values between 3.5 and 4.5 (Foditsch et al, 2014). This suggests that pH influences F. prausnitzii distribution along the gut.…”
Section: Effect Of Gut Physicochemical Conditionsmentioning
confidence: 99%
“…These bacteria can also enhance colonocyte growth and function through the production of VFA. For instance, Fusobacteria, Faecalibacterium, Blautia, Lachnospiraceae, and Butyricicoccus are butyrate-producing bacteria [39][40][41]. Butyrate is the major energy substrate for colonocytes, and provides many benefits to heifer calves such as improved epithelial tight junctions and reduced inflammatory status [42].…”
Section: Hindgut Microbiome and Metabolome During The Preweaning Perimentioning
confidence: 99%